Utilization of Assistive Technologies for Information Support for Differently Abled Persons: Enhancing education through assistive technologies (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Technology is essential to the education of all children, but particularly that of individuals withlearning disabilities. Technology both allows and empowers persons with disabilities by providing theoption of greater full inclusion in meaningful educational experiences. As a result, technologicaladvancements, especially those based on information and communication technology (ICT), areessential for providing special needs kids with the appropriate learning environment and meeting theireducational needs. Technology is playing a growing role, either directly or indirectly, in how peoplelive their everyday lives. Technology enhances education quality and promotes more studentparticipation by simplifying communication and information exchange. As a result, technology isessential to the preparation of educators. The purpose of the study is to determine how assistivetechnologies are used to support information for people with disabilities.